Human genetic susceptibility to intracellular pathogens - Vannberg, Fredrik O; Chapman, Stephen J; Hill, Adrian V.S (Immunological reviews, 2011)
Intracellular pathogens contribute to a significant proportion of infectious disease morbidity and mortality worldwide. Increasing evidence points to a major role for host genetics in explaining inter-individual variation in susceptibility to infectious diseases. A number of monogenic disorders predisposing to infectious disease have been reported, including susceptibility to intracellular pathogens in association with mutations in genes of the interleukin-12/interleukin-23/interferon-γ axis. Common genetic variants have also been demonstrated to regulate susceptibility to intracellular infection, for example the CCR5Δ32 polymorphism that modulates human immunodeficiency virus-1 (HIV-1) disease progression. Genome-wide association study approaches are being increasingly utilized to define genetic variants underlying susceptibility to major infectious diseases. This review focuses on the current state-of-the-art in genetics and genomics as pertains to understanding the genetic contribution to human susceptibility to infectious diseases caused by intracellular pathogens such as tuberculosis, leprosy, HIV-1, hepatitis, and malaria, with a particular emphasis on insights from recent genome-wide approaches. The results from these studies implicate common genetic variants in novel molecular pathways involved in human immunity to specific pathogens.